The relationship of health literacy and adolescent HIV-AIDS prevention behavior: a case study of vocational school adolescents in Gowa Regency - Pusvitasari, Inda; Harma, Asmarani; Perdana, Satria; Dharma, Surya (Gema Wiralodra, 2023)
Adolescents are the group most at risk of HIV-AIDS transmission because adolescence is the period when there is the highest social mobility and will open opportunities for them to be exposed to various physical and psychological changes. As a result, these adolescents have a high vulnerability to the transmission of multiple types of diseases, including HIV-AIDS. The results of interviews with several adolescents who are students at the high school level in Gowa Regency obtained information that adolescents view and evaluate people who have HIV-AIDS. Adolescents answer that they tend to avoid and hate them. According to the explanations of several youths, this was all due to the lack of information obtained, and the school had not yet provided a curriculum on HIV-AIDS in schools. Then, the results of interviews with several high school teachers revealed that no research had been conducted related to HIV-AIDS prevention behavior. On the other hand, the incidence of communicable and non-communicable diseases is closely related to a person's health literacy. The condition of the world of health, which is increasingly more complex than various diseases, certainly requires a skill in health literacy owned by every individual, including adolescents. Based on this, a study was conducted which aimed to reveal and find out 1) the description of health literacy and HIV-AIDS prevention behavior in high school youth in Gowa District, 2) the relationship between health literacy and HIV-AIDS prevention behavior in high school youth in Gowa District. The data collection technique uses a Likert scale questionnaire, and the data analysis technique uses chis square analysis. The results of the study showed that 1) the health literacy of SMK youth in Gowa Regency was generally low, 2) the HIV-AIDS prevention behavior of VOCATIONAL SCHOOL youth in Gowa Regency was generally low, 3) there was a relationship between health literacy and HIV-AIDS prevention behavior in SMK adolescents in Gowa Regency.